NAVIGATION AIDS AS TOOLS TO SUPPORT THE DEVELOPMENT OF COMPETENCES IN THE CONDITIONS OF REALIZATION OF INDIVIDUAL EDUCATIONAL TRAJECTORY - E. F. Zeer; E. Yu. Zhurlova (Образование и наука)
Introduction. Continuing education or «education through all life» is required of the person by modern realities of the information, quickly changing society; thus, continuing education is carried out on a development trajectory, individual for each person. Maintenance of such educational process needs effective tools. The relevance of its development caused the research presented in the publication.The aim is to show the possibilities of navigation aids during realization of individual routes of the training conforming to federal state educational standards and considering the purposes and interests of each separately taken personality.Methodology and research methods. The leading methodological basis is personality-oriented approach in the implementation of individual educational trajectory. Logical-pedagogical analysis of students’ individual educational trajectory progress is used.Results and scientific novelty. The interrelation of the concepts «individual educational trajectory» and «individual educational route» is revealed. The conceptual model of maintenance of an individual educational trajectory as a set of reference points of mastering of competences necessary for the expert is offered. Navigators of educational process and cases of individual educational achievements assessment act as didactic means in model. It is shown whence application of components of models allows to: organize the professional orientation actions more effectively; exercise entrance control of knowledge prior to training; control actions during vocational training; correlate an individual trajectory of training to the standard; have a guide when studying disciplines of various cycles, when passing educational and production training, protection of final qualification work; finally, it is possible for a pupil to carry out self-estimation of the acquired competences.Practical significance. The materials of the present publication will be useful to scientific and practical workers of all education levels, and also the people who are engaged in self-education.